IMPLEMENTASI PROGRAM TAKHASSUS TERHADAP PENINGKATAN KEMAMPUAN HAFALAN DAN KEDISIPLINAN SISWA KELAS I DI MIS HIDAYATUL ATHFAL - Ardi Muhamad Arsyad; Kivtiyani Mulyadi; Puja Agisti Amelia; Aji Saputra; Alfany Wahidatusyifa; Yayu Kurniasih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe and analyze the implementation of the Takhassus program to improve students' Quran memorization skills and discipline. The Takhassus class is an intensive program designed to strengthen memorization through the muroja'ah method, regular recitation, and special coaching. This study used a qualitative, descriptive approach. The research subjects included the principal, the tahfidz teacher, and first-grade students of the Takhassus program at MI Hidayatul Athfal. Data collection techniques were conducted through observation, in-depth interviews, and documentation. Data analysis used the Miles and Huberman model: data reduction, data presentation, and conclusion drawing. Data validity was tested through triangulation of sources and techniques. The results showed that the implementation of the Takhassus program through the Ummi and Muroja'ah methods was able to improve the quality of student memorization and foster discipline through the habit of memorizing recitation, punctual attendance, and adherence to learning rules. Supporting factors included teacher commitment and parental support, while constraints included variations in student abilities and time constraints.